2022
DOI: 10.1111/pan.14414
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric spinal anesthesia at a tertiary care hospital: Eleven years after

Abstract: Anesthesia-related critical incidents in pediatric patients occurred three times more frequently than in adults and, moreover, three times higher in infants (<1 year of age) than in children (>1 year of age). The overall incidence of critical events requiring intervention is 35%, most of them related to hypotension and hypoxemia episodes, occurring during the maintenance of anesthesia. The major risk factors in children undergoing anesthesia are age (<1 year), prematurity (<37 weeks of gestation), and comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…While pediatric SpA may entail complications such as hypotension, vomiting, bradycardia, desaturation, PDPH, or postoperative apnea, the rates are low. Desaturation, one of the most important complications, was reported at a rate of 2% by Eizaga Rebollar et al 3 Caliskan et al 12 reported a complication rate of 3.4%, PDPH being the major complication. Kantekin et al 13 reported a rate of 4.8%, the most important complication being foot drop.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While pediatric SpA may entail complications such as hypotension, vomiting, bradycardia, desaturation, PDPH, or postoperative apnea, the rates are low. Desaturation, one of the most important complications, was reported at a rate of 2% by Eizaga Rebollar et al 3 Caliskan et al 12 reported a complication rate of 3.4%, PDPH being the major complication. Kantekin et al 13 reported a rate of 4.8%, the most important complication being foot drop.…”
Section: Discussionmentioning
confidence: 99%
“…These include less intraoperative desaturation and bradycardia, higher minimum systolic blood pressure with fewer intervention requirements, less heat loss, a lower incidence of postoperative early apnea, shorter anesthesia times from the conclusion of surgery to leaving the operating room, and shorter times to first feed. 3,11 An examination of the literature shows that pediatric SpA enjoys a high success rate. Studies with a similar design to the present research have reported success rates of 97.5-100%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spinal anaesthesia for infants and children serves to avoid exposure to general anaesthesia for certain surgical procedures and can be a good option for patients with significant comorbidities such as airway anomalies, cardiopulmonary disease or sequelae of prematurity [17,18 ▪▪ ]. In infants, spinal anaesthesia confers more haemodynamic stability when compared with general anaesthesia [19], obviates the need for airway instrumentation and likely improves incidence of postoperative apnoea [20] in vulnerable populations such as premature and ex-premature patients.…”
Section: Paediatric Regional Anaesthesiamentioning
confidence: 99%